The endocranial anatomy of Buriolestes schultzi (Dinosauria: Saurischia) and the early evolution of brain tissues in sauropodomorph dinosaurs. Issue 4 (2nd November 2020) - Müller, Rodrigo T.; Ferreira, José D.; Pretto, Flávio A.; Bronzati, Mario; Kerber, Leonardo
Abstract: Our knowledge on the anatomy of the first dinosaurs (Late Triassic, 235–205 Ma) has drastically increased in the last years, mainly due to several new findings of exceptionally well‐preserved specimens. Nevertheless, some structures such as the neurocranium and its associated structures (brain, labyrinth, cranial nerves, and vasculature) remain poorly known, especially due to the lack of specimens preserving a complete and articulated neurocranium. This study helps to fill this gap by investigating the endocranial cavity of one of the earliest sauropodomorphs, Buriolestes schultzi, from the Upper Triassic (Carnian—c. 233 Ma) of Brazil. The endocranial anatomy of this animal sheds light on the ancestral condition of the brain of sauropodomorphs, revealing an elongated olfactory tract combined to a relatively small pituitary gland and well‐developed flocculus of the cerebellum. These traits change drastically across the evolutionary history of sauropodomorphs, reaching the opposite morphology in Jurassic times. Furthermore, we present here the first calculations of the Reptile Encephalization Quotient (REQ) for a Triassic dinosaur. The REQ of B. schultzi is lower than that of Jurassic theropods, but higher than that of later sauropodomorphs. The combination of cerebral, dental, and postcranial data suggest that B. schultzi was an active small predator, able to track moving prey. Abstract : The first complete endocast of an early dinosaur is presented. The endocranium of Buriolestes schultzi reveals relatively small olfactory bulbs, an elongated olfactory tract, a small pituitary fossa, and well‐developed flocculus of the cerebellum. The data support B. schultzi as an active small predator, which was able to track moving prey. These endocranial traits change drastically across the evolutionary history of sauropodomorphs, reaching the opposite morphology in Jurassic times.